Ovipositional response of podfiy (Melanagromyza obtusa) on resistant pigeonpea (Cajanus cajun) selections - LAL, S S; YADAVA, C P (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during rainy seasons (kharif) of 1987-R8, 1989-89 and 1989-90 to study the mechanism of redgram pndfly (Melanagromyza obtusa Malloch) in 25 pigeonpea [Cajanus cajan (L.) Millsp.] selections differing in resistance and susceptibility. Resisrant selections ’SL 12-2’,’SL 42-3’,’ ICP 7946 ’.’ICP 7151’,’GP3-3’ and ’ICP 8102’showed consistently low (11-14%) grain damage by podfly compared with susceptible selections ’CODE 3’. ’ICP 7050’,’D3’ and’ JM 2412’ (27-33% grain damage). The ovipositioni (%) and relative resistance (%) ratings of podfly were positively correlated, Thus low grain damage in the pigeonpea selections considered resistant to podfly is mainly due to low preference for oviposition by the podfly.